MENYOROT FENOMENA CADAR DI INDONESIA - Mubakkirah, Fadhliah (Musawa: Journal for Gender Studies, 2020)
Since the emergence of veil use in Indonesia, it has always been a hot issue to discuss, such as legal (Syariah) differences (khilafiyah issues), is it cultural or not, and it considered a symbol of radicalization. The most recent discourse is the ban on the use of the veil by the Minister of Religion to be polemic in the society, there are those who support with security reasons, and also those who reject it because they regard it as an expression of religious practice. The discussion about the use of veil became a response to the phenomenon that occurs in the community.